(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
In this article, Uzbekistan-83 variety of fodder beet was planted in three different sowing schemes: 70x15-2, 70x20-2, 70x25-2, and the effect of Tandem biostimulator on the development of roots was studied. Tandem biostimulant application at a low rate of 0.4 liters per hectare led to an increase in root fruit yield, while Fitovak (Etolon) biostimulant was used at a rate of 300 ml/ha to show a high rate.